(untitled) (Revista Contexto & Educação, 2022)
The objective of the article is to trace a panorama of some possible relationships between the teaching of art and the Professional Education offered by the Federal Institutes of Education, Science and Technology, problematizing the duality between general education and professional education, from the perspective of integrated education. Data analyzed with the bricolage method are presented in a qualitative research on the presence of teachers and courses in Visual Arts, Theater, Dance and Music in the IFs, which combined with a theoretical discussion about art, power and resistance based on Foucault, indicate that teaching art can be configured as a strategy of resistance against the neoliberal performative model current in this teaching system.